EndNote at Lehigh. - Sharon L. Siegler; Brian Simboli (Issues in Science and Technology Librarianship)
We detail the experiences of librarians in implementing campus-wide use of EndNote, a citation management software package and describe a variety of approaches that librarians at other institutions may wish to employ. Librarian effort in promotion and support of EndNote is a rewarding way to enhance the library's presence on campus because of the close interaction with faculty and graduate students.